Nucleic acid extraction and multiplex analysis for simultaneous detection of the corn stunt complex pathogens in plant and insect tissues - Gorayeb E.S.* (2023)
© 2022, The Author(s), under exclusive license to Sociedade Brasileira de Fitopatologia.The corn stunting complex (CSC), composed of two Mollicutes (phytoplasma and spiroplasma) and one marafivirus (maize rayado fino virus, MRFV), is the most important phytosanitary problem of maize crops in Brazil. Currently, MRFV detection is performed separately from mollicutes, which contributes to the omission of virus detection in CSC monitoring activities and basic studies. Here, a complete diagnostic method for simultaneous detection of CSC pathogens is presented, comprising the optimization of an RNA/DNA extraction protocol and a triplex PCR, in which a newly designed MRFV-specific primer pair was included along with the widely used R16F2n/R2 and CSSF2/CSSR6 primers for the mollicutes. As a result, a newly designed MRFV-specific primer targeting the 5′ end of the polyprotein gene was developed and efficiently amplified MRFV from different geographical locations and tissues (plant and insect) in the multiplex reaction. The designed MRFV primer pair was species-specific, sensitive, and did not form secondary structures or dimerize with each other, nor with the other primers used to detect the mollicutes. This method proved to be effective, cheaper, faster, and easier to perform than other methods previously reported. Thus, it is a helpful tool for both basic and applied studies as well as monitoring programs aiming to understand the MRFV presence in the CSC and maize crops.